Acute hormonal findings after aneurysmal subarachnoid hemorrhage – report from a single center. (3rd April 2017) - Takala, Riikka S. K.; Kiviranta, Riku; Olkkola, Klaus T.; Vahlberg, Tero; Laukka, Dan; Kotkansalo, Anna; Rahi, Melissa; Sankinen, Matti; Posti, Jussi; Katila, Ari; Rinne, Jaakko
ABSTRACT: Purpose : The aim was to assess anterior pituitary hormone levels during the acute phase of aneurysmal subarachnoid hemorrhage (aSAH) and analyze the possible association with the clinical condition and outcome.Material and methods : Forty patients with aSAH whose aneurysm was secured by endovascular coiling were enrolled. Basal secretions of cortisol, testosterone, luteinizing hormone (LH), prolactin (PRL), and sex hormone binding globulin (SHBG) levels were measured up to 14 days after the incident.Results : The main finding was that hypocortisolism was rare whereas testosterone deficiency was common in male patients. Furthermore, various other hormone deviations were frequent and there was wide interindividual variability. We found no association between delayed cerebral ischemia (DCI), outcome of the patients or aneurysm location, and hormone abnormalities, while both Hunt & Hess and Fisher grade were associated with low PRL levels. Hunt & Hess 5 was associated with low PRL concentration when compared to grades 1 (OR = 4.81, 95% CI 1.15–20.14, p = 0.03), 3 (OR 7.73, 95% CI 1.33–45.01, p = 0.02), and 4 (OR = 6.86 95% CI 1.28–26.83, p = 0.02). Fisher grade 4 was associated with low PRL concentration when compared to grades 3 (OR 3.37, 95% CI 1.06–10.73, p = 0.03) and 2 (OR 9.71, 95% CI 1.22–77.10, p = 0.04).Conclusion : Deviations from normal and huge interindividual differences are common in hormone levels during the acute phase of aSAH. Routine assessment of anterior pituitary function in the acute phase of aSAH is not warranted. During the follow-up in the outpatient clinic, hormone concentrations were not measured, which would have brought a more long-term perspective into our findings.